Decision Support System of Bonus for Honorary Teachers through the TOPSIS Algorithm - Kurniawan, Angga; Kusrini, Kusrini (PT Mattawang Mediatama Solution, 2024)
The proliferation of algorithms facilitates various tasks by allowing for specialization in specific fields. Among these, algorithms designed for calculation and decision-making are particularly useful. Decision Support Systems (DSS) have undergone numerous changes and advancements, leading to the development of new algorithms in this area. The TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) algorithm enables the determination of criteria and weights to assist in decision-making by calculating solution distances and weight values. This system allows for the adjustment of points, criteria, and weight values based on specific needs. At SMPN 1 Pajangan, the implementation of this system enhances the accuracy and efficiency of supervisors in managing bonuses for non-permanent teachers, mitigating social jealousy through a predefined, system-based distribution of criteria and weights.